Sorption isotherms of new types of zeolites and soils for some heavy metals - Zin,M. (2015)
The sorption isotherms of newly available zeolites and two soil samples for heavy metal ions of Pb, Cu and Cd have been investigated. Experimental measurements have been made on the batch sorption of heavy metal ions from respective solutions using a single sample. All metal ions concentration in solutions of both initial and equilibrium condition have been measured by using atomic absorption spectrometry. The applicability of the Langmuir and Freundlich models for the different sorbent materials was tested. The coefficient of determination (R2) of both models were generally quite good varying from 0.84 to 0.99 which indicates that both models adequately describe the experimental data of the sorption of these metals. In addition, most of the sorption isotherms of studied sorbent materials for studied heavy metal ions were better fitted and could be described more moderately with Langmuir isotherms, except for the sorption isotherms of zeolite 2 and soil 1 for Cd2+, which were better fitted with Freundlich isotherms. This research shows that zeolite sample 1 for Pb2+, soil 1 for Cu2+ and soil 2 for Cd2+ions may have higher affinity among studied sorbent materials due to their lower "a" values for respective metal ions. The maximum sorption quantity for Pb2+ can be found on zeolite 1, that for Cu2+ on soil 1 and that for Cd2+ on soil 2. This study could be extended for the estimation of contamination and removal of these cationic heavy metals and give a hand to environment to be healthy and safe.